Joanita Vroom. Byzantine to Modern Pottery in the Aegean. An Introduction and Field Guide. - Bintliff, John (Journal of Greek Archaeology, 2017)
This is the second edition (the first was 2005) of an extremely useful field guide to ceramics in the post-Roman Aegean. It is exceptionally well-illustrated, well cross-referenced, and goes well beyond earlier studies in giving scope to cooking and household wares alongside the better-known tablewares of the Medieval and Post-Medieval periods. Joanita Vroom’s wide involvement in projects across many regions of Aegean Greece, Albania and Mainland Turkey have allowed her firsthand experience of the wide variety of ceramic products in time and space, both from survey and excavation contexts.